Caracterização das vesículas extracelulares liberadas por tripomastigotas do Trypanosoma cruzi sob distintas condições de estresse biológico - Vasconcelos, Camilla Ioshida [UNIFESP] (2019)
Chagas disease caused by T. cruzi is a neglected tropical disease that affects 8 million people worldwide. Trypomastigotes release extracellular vesicles (EVs) that are composed of the main surface molecules of the parasite. The aim of this study was to verify differences between EVs from different T. cruzi strains, to evaluate the release of EVs by trypomastigotes incubated under different stress conditions and the immunomodulatory role of these EVs in preactivated bone marrow-derived macrophages (BMDM), as well as to evaluate the chemotherapeutic purpose of compounds against T. cruzi considering drug reuse and hybridization approaches. We observed qualitative and quantitative differences between Y and YuYu strains EVs of T. cruzi, these differences directly affect virulence and infectivity rate in macrophages and epithelial cells. Futhermore, viability and/or integrity of the parasite is important for the release of EVs. These nanoparticles trigger a more proinflammatory response in the host cell in short term, which may be a strategy developed by the parasite to create a more favorable environment for their establishment in the host. Chemotherapeutic studies have shown that POA and TS9 compounds evaluated through reuse and hybridization approaches, respectively, may be promising molecules for the development of new therapeutic strategies for Chagas disease, which is a difficult to treat and control disease.